THE GENESIS OF SCIENTIFIC IDEAS TO LIMIT PUBLIC AUTHORITIES - Kotukov O. A. (Pressing Problems of Public Administration, 2016)
The paper considers the evolution of scienti c ideas about the limits of public power. It has been determined that most researchers who have studied the issue, insisted on the need for safeguards against state power usurpation and abuse. The analysis allowed classifying these safeguards by the following criteria: geographic, legal, social, property, organizational and others.